Sharenting, Exploitation, or Entertainment? Case Study of @abe_daily TikTok Accounts and Their Impact on Children's Privacy - Anggraeni, Maulinda; Adinugraha, Hendri Hermawan (RaSAIL Media Group, Semarang, Indonesia, 2024)
Sharenting is a practice where parents share their children's life moments on social media. The study focused on @abe_daily's TikTok account, which features videos of a child's daily life and has sparked debate about children's privacy and potential exploitation. The main issue in this study is how the public views the content, whether it is as family entertainment or a form of child exploitation. This study aims to understand the public's perception of sharenting in @abe_daily accounts and its impact on children's privacy. This study uses a mixed methods approach, with in-depth interviews with ten informants and a survey of 13 respondents familiar with the account. Qualitative analysis was done through thematic, while quantitative data was collected through Likert scale questionnaires. The results showed that most respondents viewed content as positive entertainment, but there were concerns about child exploitation and privacy. While monetization of children's content is considered acceptable as long as children's well-being is maintained, there is an urgent need for stricter regulations regarding children's privacy on social media. This study recommends increased digital education for parents and clearer policies to protect children's rights in sharenting.